Light quality, oxygenic photosynthesis and more - Lazar, D; Stirbet, A; Björn, L O; Govindjee, G (Photosynthetica, 2022)
Oxygenic photosynthesis takes place in thylakoid membranes (TM) of cyanobacteria, algae, and higher plants. It begins with light absorption by pigments in large (modular) assemblies of pigment-binding proteins, which then transfer excitation energy to the photosynthetic reaction centers of photosystem (PS) I and PSII. In green algae and plants, these light-harvesting protein complexes contain chlorophylls (Chls) and carotenoids (Cars). However, cyanobacteria, red algae, and glaucophytes contain, in addition, phycobiliproteins in phycobilisomes that are attached to the stromal surface of TM, and transfer excitation energy to the reaction centers via the Chl a molecules in the inner antennas of PSI and PSII. The color and the intensity of the light to which these photosynthetic organisms are exposed in their environment have a great influence on the composition and the structure of the light-harvesting complexes (the antenna) as well as the rest of the photosynthetic apparatus, thus affecting the photosynthetic process and even the entire organism. We present here a perspective on 'Light Quality and Oxygenic Photosynthesis', in memory of George Christos Papageorgiou (9 May 1933-21 November 2020; see notes a and b). Our review includes (1) the influence of the solar spectrum on the antenna composition, and the special significance of Chl a; (2) the effects of light quality on photosynthesis, measured using Chl a fluorescence; and (3) the importance of light quality, intensity, and its duration for the optimal growth of photosynthetic organisms.
Keywords: chromatic acclimation of cyanobacteria; Chl fluorescence induction; photoreceptors; stomatal and chloroplast photoinduced movements; photosystems I and II; photosynthetic pigments